2017
DOI: 10.1111/1751-7915.13028
|View full text |Cite
|
Sign up to set email alerts
|

Semicontinuous sophorolipid fermentation using a novel bioreactor with dual ventilation pipes and dual sieve‐plates coupled with a novel separation system

Abstract: SummarySophorolipids (SLs) are biosurfactants with widespread applications. The yield and purity of SLs are two important factors to be considered during their commercial large‐scale production. Notably, SL accumulation causes an increase in viscosity, decrease in dissolved oxygen and product inhibition in the fermentation medium. This inhibits the further production and purification of SLs. This describes the development of a novel integrated system for SL production using Candida albicans O‐13‐1. Semicontinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 27 publications
0
26
0
1
Order By: Relevance
“…However, few studies have reported the effect of the viscous nature of the fermentation broth on microbial growth and productivity. An increase in the concentration of hydrophobic substrates causes an increase in broth viscosity, a decrease in dissolved oxygen, and product inhibition in the fermentation medium (Zhang et al, ). In case of SAO, increasing the concentration from 60 to 80 g L −1 leads to a decrease in biomass due to oxygen limitation hence reducing the productivity.…”
Section: Resultsmentioning
confidence: 99%
“…However, few studies have reported the effect of the viscous nature of the fermentation broth on microbial growth and productivity. An increase in the concentration of hydrophobic substrates causes an increase in broth viscosity, a decrease in dissolved oxygen, and product inhibition in the fermentation medium (Zhang et al, ). In case of SAO, increasing the concentration from 60 to 80 g L −1 leads to a decrease in biomass due to oxygen limitation hence reducing the productivity.…”
Section: Resultsmentioning
confidence: 99%
“…It is hard to meet those prerequisites if using the anthrone method on crude culture broth: other sugars, either derived from the supplemented carbon source or from cell wall components, are also present and not every laboratory uses sophorolipid as a standard for the calibration curve. Hence, practices where sophorolipid concentration is determined by applying the anthrone method to measure total carbohydrate, followed by subtraction of glucose concentration obtained by another method, are questionable (Zhang et al ., 2018). Nevertheless, both orcinol and anthrone reagent can be used as detection reagent for glycolipids upon thin‐layer chromatography (TLC) analysis, as discussed below.…”
Section: Critical Review Of Experimental Colorimetric Methodologies Fmentioning
confidence: 99%
“…Also, as a platform yeast, several new‐to‐nature glucolipids were created such as bolaform sophorolipids that have attractive properties. The highest titer and volumetric productivity being reported currently are 477 g L −1 and 3.7 g L −1 h −1 respectively with specific bioprocessing optimization . However, it is important to consider the highest productivity reported by Gao et al .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The highest titer and volumetric productivity being reported currently are 477 g L −1 and 3.7 g L −1 h −1 respectively with specific bioprocessing optimization. 35,51 However, it is important to consider the highest productivity reported by Gao et al 51 As they mentioned, their purpose was to verify the feasibility of enhancing volumetric productivity by means of high-cell-density fermentation. Their experimental design was more likely to detect the productivity limitation of S. bombicola.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation